Estudo de conteúdos avaliados nos exames do ENADE 2013 e 2016 e REVALIDA 2015 e 2016 e sua correlação com a matriz de correspondência curricular do REVALIDA - CARVALHO, A. B. (2018)
Assessment is essential for analyzing the quality of medical formation and fundamental to the development and improvement of educational activities, and should be based on both competencies and content. External evaluations of medical courses, prepared by regulatory bodies, indicate the contents considered essential or more relevant from the point of view of these bodies. Therefore, identifying inferred learning objectives in these assessments could help teaching institutions and students to understand what is expected from them. The present study verifies the agreement between the content evaluated by the ENADE exams 2013 and 2016 and REVALIDA 2015 and 2016 and the content of the Matrix of Curricular Correspondence Revalida (Revalida Matrix). It was analyzed if the contents of the Revalida Matrix were evaluated by ENADE and REVALIDA in the mentioned years, and the contents were compared in the respective evaluations, determining concordances and discrepancies between them. Methodology: The specific contents addressed in the written exams of ENADE 2013 and 2016 (last two years of test application and after the publication of the Revalida Matrix) and REVALIDA 2015 and 2016 (last two years of test application and after 2014 when it acquired new formatting) were verified on both multiple choice and discursive items. The contents explored in these evaluations were compared with those of the Revalida Matrix, establishing the relation of contents between them. Results: The analysis of the contents of the REVALIDA Matrix (n = 749 subjects)contained in the evaluations studied revealed a lower content range in ENADE when compared to REVALIDA. When associated the contents discussed in the 4 evaluations, it was found a large number of Revalida Matrix themes that were not addressed in any of the tests analyzed. Conclusion: The evaluations of ENADE and REVALIDA have different scope regarding the use of the contents contained in the Revalida Matrix. The third part of the Revalida Matrix themes were not addressed in the evaluations studied.